2024
DOI: 10.18063/ijb.v4i1.120
|View full text |Cite
|
Sign up to set email alerts
|

An nMgO containing scaffold: Antibacterial activity, degradation properties and cell responses

Abstract: Bone repair failure caused by implant-related infections is a common and troublesome problem. In this study, an antibacterial scaffold was developed via selective laser sintering with incorporating nano magnesium oxide (nMgO) to poly(3-hydroxybutyrate-co-3-hydroxyvalerate) (PHBV). The results indicated the scaffold exerted high antibacterial activity. The antibacterial mechanism was that nMgO could cause oxidative damage and mechanical damage to bacteria through the production of reactive oxygen species (ROS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 67 publications
(84 reference statements)
1
14
0
Order By: Relevance
“…Some of the previous studies confirmed that hydration of MgO NPs and formation of hydroxide leads to the surface bond electro‐hole pairs that decompose into surface trapped electrons and localized holes which are strong catalysts for ROS production via single electron reduction . These facts were used as explanation of the ROS‐mediated antimicrobial activity in MgO NPs . However, it is important to note that in this report we showed that generated quantities of ROS did not affect the activity of the MgO NPs because none of the ROS inhibitors influenced their antibacterial activity.…”
Section: Discussionsupporting
confidence: 56%
“…Some of the previous studies confirmed that hydration of MgO NPs and formation of hydroxide leads to the surface bond electro‐hole pairs that decompose into surface trapped electrons and localized holes which are strong catalysts for ROS production via single electron reduction . These facts were used as explanation of the ROS‐mediated antimicrobial activity in MgO NPs . However, it is important to note that in this report we showed that generated quantities of ROS did not affect the activity of the MgO NPs because none of the ROS inhibitors influenced their antibacterial activity.…”
Section: Discussionsupporting
confidence: 56%
“…It has been reported that CuNPs of about 30 nm are more active against pathogens than those of smaller size [ 33 ]. CuONPs have received much attention in a wide range of applications, including their use as antimicrobial agents [ 9 , 34 , 35 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…[5,18,[92][93][94] This technique is preferred over several other methods (including melt-spinning and 3D printing) due to the high surface area-to-volume ratio that can be achieved and the relatively large number of inter-and intrafiber pores obtained in the fibers. [95][96][97][98] The electrospinning process employs electrostatic forces to produce polymeric fibers, in which various parameters such as applied voltage, polymer concentration, solvent, tip-to-target distance, and spinneret gauge size influence the quality of the fibers. [18] In practice, a polymeric solution in a volatile solvent is fed at a controlled rate to a needle that serves as the spinneret, via a syringe pump.…”
Section: Electrospinning Overviewmentioning
confidence: 99%